Study on correlation between pore development and strength characteristics of tar-rich coal in different coal seams - SHEN Yanjun; MA Wen; WANG Xu; SHI Qingmin; ZHANG Lei; LYU You; XU Hanhua (Meikuang Anquan, 2023)
In the process of coal mining, the coal body is subjected to external force, resulting in pore penetration and strength decline, which is easy to cause engineering disasters such as roadway surrounding rock instability and roof collapse. In order to study the correlation and influence mechanism between pore distribution and strength characteristics, three groups of representative coal samples （N22, H52 and H42 coal samples） from Yushenfu Mining Area in northern Shaanxi Province of China were selected to carry out the pore size distribution and strength characteristics tests, and the results were analyzed based on Pearson correlation coefficient and energy evolution. The research conclusions are as follows: the three groups of coal samples are mainly developed with micropores and transition pores, and the development of macropores is extremely poor. The compressive strength of N22 coal sample is the highest, which is 31.3 MPa, followed by H52 and H42 coal samples, which are 14.2 MPa and 12.5 MPa, respectively. The total porosity of coal samples and the porosity of large pores, middle pores and transition pores are negatively correlated with compressive strength, and the porosity of micropores is positively correlated with compressive strength. During the compression process, the micropore is beneficial to the accumulation of elastic strain energy Ue during the compression of coal samples, and to a certain extent, it is beneficial to improve the compressive capacity of coal samples. Large pores, middle pores and transition pores consume dissipation energy Ud and form cracks through each other.